2011
DOI: 10.1186/1550-2783-8-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of dietary supplements in Olympic athletes is decreasing: a follow-up study between 2002 and 2009

Abstract: BackgroundThe aim of this study was to assess the frequency of use of dietary supplements (DS) among large sample of elite Finnish athletes and to describe possible changes in dietary supplement use between the years 2002 and 2009.MethodsA prospective follow-up study was conducted on Olympic athletes. The first survey was conducted on Olympic athletes in 2002 (N = 446) and the follow-up study was conducted between May 2008 and June 2009 (N = 372).ResultsIn 2002, a total of 81% of the athletes used dietary supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
36
5
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 23 publications
9
36
5
4
Order By: Relevance
“…For example, a survey of Olympic-caliber Finnish athletes indicated that 16% ( n  = 446) used creatine in 2002 and 8% ( n  = 372) used creatine in 2009 [153]. Creatine use in Canadian Olympians was somewhat more common during the Atlanta (14%; n  = 257) and Sydney Olympic Games (12%; n  = 300) [154].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a survey of Olympic-caliber Finnish athletes indicated that 16% ( n  = 446) used creatine in 2002 and 8% ( n  = 372) used creatine in 2009 [153]. Creatine use in Canadian Olympians was somewhat more common during the Atlanta (14%; n  = 257) and Sydney Olympic Games (12%; n  = 300) [154].…”
Section: Discussionmentioning
confidence: 99%
“…The use of anti-asthmatic medication among OAs is known to be common and there may even be overuse of asthma medications in certain athletic disciplines. 5,[11][12][13][14][15][16] On the other hand, the diagnostic criteria for athletes' asthma may be too strict so that athletes suffer from asthma symptoms but they are not able to get asthma diagnosis. This topic has been discussed in detail in an article published by our study group.…”
Section: Discussionmentioning
confidence: 99%
“…A more detailed description of the types of sports of the OAs has been provided previously by our study group. 4,5 Paralympic athletes represented individuals participating in a total of 14 different winter and summer sports. The types of sports of the PAs are given in Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…Optimising nutritional intake has been demonstrated to elicit peak performance levels [1,2,3] from subsequent enhancement of recovery processes, body mass control, effective hydration, reductions in illness and injury, coinciding with increased confidence as a result of a more prepared mental state for competition [4]. Irrespective of the competition level and type of sport prolonged energy deficit may lead to decreased performance and health, including iron deficiency anemia and immunosuppression [5].…”
Section: Introductionmentioning
confidence: 99%